INTERACTIVE TRAINING METHODS OF TEACHING ECOLOGICAL AND PEDAGOGICAL DISCIPLINES AT HIGHER EDUCATIONAL INSTITUTIONS - Mariya Skyba (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article explains the terms "interactive training methods", "interactive training techniques" and "interactive training". The meaning of interactive training in the process of future biology teachers preparation has been clarified. The examples of the application of the interactive training methods and techniques while teaching ecological and pedagogical disciplines such as "Techniques of ecological education" and "Organization of ecological and pedagogical activity" (both during practical classes and lectures) have been provided. The usage of interactive training methods and techniques proves to make students interact efficiently, cooperate, teach each other, it creates the feeling of individual success and helps to form organizational skills of ecological and pedagogical activity.